Peningkatan Literasi Digital untuk Aktualisasi Diri Santriwati di Pondok Pesantren - Gilang Primajati; Dodiy Firmansyah; Agus Sofian Eka Hidayat; Siti Soraya; Wirajaya Kusuma (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
The rapid development of digital technology has influenced educational patterns and styles in Islamic boarding schools. To increase learning efficiency and wider access to information, the digital world also provides new means for obtaining and communicating religious ideas and opinions. However, concerns arise regarding the potential negative impact of digital media which could erode Islamic boarding school culture and traditions such as the tradition of face-to-face learning (mumukaah), searching for references through Turast books/books (istimbat), and direct interaction between teachers (ustadz) and students. The use of cellphones, laptops and smart TVs as learning media presents its own challenges. Responding to this situation, the aim of the service is to collaborate to provide actualization of digital literacy for female students, the asatidaz board and supervisors at the Hikmatusysyarief Salut Narmada Islamic Boarding School. This activity is a manifestation of the university's active role in supporting digital literacy among Islamic boarding schools to prepare Indonesia's golden generation in 2045. The implementation method uses a visual integrative thinking method approach, which combines various methods such as visualization of integrative ideas, informative lectures, open discussions, and reflection. in-depth and problem-solving based on students' real experiences during the learning process in Islamic boarding schools. In conclusion, digital literacy for female students' self-actualization is very important. This can increase the self-confidence of female students to respond to the challenges of this modern era and avoid negative digital behavior.